HUBUNGAN SISA MAKANAN DENGAN TINGKAT KEPUASAN TERHADAP KUALITAS MAKANAN PADA LANSIA PROGRAM PERMAKANAN DI KELURAHAN DUKUH MENANGGAL SURABAYA - Ayu Adhianti, Azizah; Ruhana, Amalia (Cahaya Ilmu Bangsa Institute, 2025)
The purpose of the Food Service program is to increase public awareness of the problems of Social Welfare Problem Inviters (PMKS). Food quality greatly influences the food service process. This activity aims to meet the nutritional needs of the elderly served by the institution. In the context of traveling abroad, the quality of a food, including taste, aroma, consistency, crispness, appearance, level of maturity, and menu variety, is always related to high food waste and low levels of satisfaction. This study aims to determine the average food waste, level of satisfaction with food quality, and the relationship between food waste and the level of satisfaction with food quality in the food program in Dukuh Menanggal Village. This study was conducted using a quantitative approach, with respondents all elderly recipients of the food program. During data collection, there were 40 elderly respondents. Data were collected using a questionnaire using a Likert scale to measure respondent satisfaction with food quality and the Visual Comstock method to measure food quality. Data analysis was carried out using the Chi-Square test. The study findings showed that while 19.78% of respondents said they had food waste, 71.32 percent said they were concerned about the quality of the food served. Even when the satisfaction level was quite high, the analysis results showed a significant relationship between food waste and satisfaction level regarding food quality (p = 0.002). This study provides important insights for institutions to improve the efficiency and quality of food programs.